Peran guru pendidikan agama Islam sebagai motivator dalam pembentukan karakter terpuji di MIM Program Khusus Putat - Erni Susilowati; Mujiburrohman Mujiburrohman; Meti Fatimah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The aims of this study were (1) to find out the relationship between the role of PAI teachers and the formation of commendable character. (2) Knowing the relationship between teacher motivators and the formation of commendable character. (3) Knowing the relationship between the role of the PAI teacher as a motivator in the formation of commendable character. This study uses a quantitative approach to the research method used is a survey method with correlation techniques using multiple linear regression analysis test. This correlation technique is used to analyze the relationship between the independent variables, namely the role of the PAI teacher (X1) and the motivator (X2) with the dependent variable, namely the formation of commendable character (Y). The population of this study was students at the MIM Putat Special Program, totaling 30 students of class IV Putat Special Program. The sample in this study were all members of the population, namely all students in the Putat Special Program, totaling 30 fourth-grade students in the Putat Special Program. Based on data analysis, it can be concluded that: (1) There is a positive relationship between the role of PAI teachers and the formation of commendable character. This is evidenced by the t count > t table (4.445 > -2.052), (2) There is a positive relationship between teacher motivators in the formation of commendable character. This is evidenced by the t count > t table (-1.494 > -2.052). This is evidenced by the t count > t table (1.488> -2.052) and the values of multiple linear regression are Y'= 4.105+1.434X1+-0.445X2.